Vegetativnoe obespecenie rabotosposobnosti sportsmenov v processe trenirovocnych meroprijati - Iordanskaya, F. A.; Tsepkova, N. K. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The results of this work are based on research and analysis of a large group of athletes (179 people) of different ages and sexes: 7-11 years old, 12-14 years old, 15-17 years old, groups of 19 years and older (77 people) and 201 highly qualified adults athletes of different sports. It has been established that with age and experience in training young athletes, an economical parasympathetic type of vegetative support is formed. The distinct differences in the autonomic regulation of heart rhythm for children of accelerates and retardants, as well as men and women, were revealed. Based on cluster analysis, a typology of autonomic provision of the ratios of autonomic provision of working capacity for athletes with different orientations of training activity was determined. Based on the correlation analysis, the orientation of changes in the mechanisms of regulation of the heart rhythm in athletes at the stage of the competitive period is revealed compared with the preparatory one in the formation of optimal relationships between indicators of autonomic performance and maintaining centralization of heart rhythm control.